2020
DOI: 10.1101/2020.05.18.101485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does the human placenta express the canonical cell entry mediators for SARS-CoV-2?

Abstract: The pandemic of coronavirus disease 2019 caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has affected over 3.8 million people, including pregnant women. To date, no consistent evidence of vertical transmission for SARS-CoV-2 exists. This new coronavirus canonically utilizes the angiotensin-converting enzyme 2 (ACE2) receptor and the serine protease TMPRSS2 for cell entry. Herein, building upon our previous single cell study of the placenta (Pique-Regi, 2019), another study, and new … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 102 publications
7
60
1
Order By: Relevance
“…Like ACE2, DPP4 was detected in all the cell types of the first trimester placenta and also in EVTs of the second trimester; very few STBs expressed ANPEP. Similar observations are made using different datasets of scRNA-seq of first trimester human placenta (Pique-Regi et al, 2020;Singh et al, 2020). In addition to the first and second trimester placenta, ACE2, TMPRSS2, BSG, ANPEP, and DPP4 transcripts are also detected in human term placenta by bulk RNA-seq.…”
Section: Discussionsupporting
confidence: 76%
“…Like ACE2, DPP4 was detected in all the cell types of the first trimester placenta and also in EVTs of the second trimester; very few STBs expressed ANPEP. Similar observations are made using different datasets of scRNA-seq of first trimester human placenta (Pique-Regi et al, 2020;Singh et al, 2020). In addition to the first and second trimester placenta, ACE2, TMPRSS2, BSG, ANPEP, and DPP4 transcripts are also detected in human term placenta by bulk RNA-seq.…”
Section: Discussionsupporting
confidence: 76%
“…(37,38). Thus, we finally used single-cell analysis of the syncytiotrophoblast, villous cytotrophoblast, and extravillous trophoblasts -the fetal component of the placenta -that confirmed the low-levels of expression of the canonical entry receptor ACE2 and TMPRSS2 genes (21,22). Conversely, we found that these cells express high-levels of DPP4 and CTSL, two potential mediators of SARS-Cov-2 host cell entry (27,30) that may contribute to the SARS-CoV-2 infection (17,25,26).…”
Section: Discussionmentioning
confidence: 87%
“…Recent literature has shown placenta cells infected with SARS-CoV-2 in pregnant women diagnosed with moderate to severe COVID-19 (17,25) with findings supporting the possibility of vertical transmission of SARS-CoV-2 (17,26). However, few placenta cells express ACE2 and TMPRSS2 (21,22) required for virus entry, raising the question about whether potential non-canonical molecular mechanisms may be involved in the biological cycle of the virus in these cells. Here, we demonstrated by transcriptomic analyses (microarray and scRNA-Seq) and in silico predictions of virus-host protein-protein interactions that, despite low-levels of ACE2 and TMPRSS2, villous trophoblast cells express high levels of the potential non-canonical cell-entry mediators DPP4 and CTSL.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, intestinal organoids derived from both human and horseshoe bats are fully susceptible to SARS-CoV-2 infection and sustain robust viral replication. Although vertical transmission of SARS-CoV-2 seems to be anecdotal, it is still unclear if this lack of infection relates to the inability of the virus to migrate through the placenta 30 , to the low susceptibility of the fetal cells to infection, or simply on low viremic loads. Whereas human fetal intestinal organoids have already been reported 20 , a reliable 3D culture in vitro model of human gastric mucosa at different developmental stages has been challenging to achieve.…”
Section: Discussionmentioning
confidence: 99%